Review Study on Heavy Metal Concentrations in Medicinal Plants and Spices - Fatimah Mohammed Abdulrahman; Haniya Muammar Muhammad Khalifa; Mabrouka Mohamed Muftah Abuamoud; Houria L Metraw; Rabeeah Ali Misbah (African Journal of Advanced Pure and Applied Sciences, 2025)
Medicinal plants and spices are widely used worldwide for their medicinal and culinary properties. However, increasing pollution and industrial activities have led to the contamination of these plants with heavy metals, posing significant health risks to consumers. This review aims to provide a comprehensive overview of the levels of heavy metal concentrations in medicinal plants and spices, their sources, and potential health effects. The study also discusses the factors affecting the accumulation of heavy metals in these plants and the methods used for their detection and quantification. Furthermore, the review highlights the need for stringent regulatory measures to ensure the safety and efficacy of medicinal plants and spices.